Very late relapse of Burkitt's lymphoma in an EBV-negative patient after 20 years of complete remission - Kmar Mrad; Nader Slama; Nouha Ben Abdeljalil; Zaineb Mlayah; Wiem Boufrikha; Abdelfattah Zakhama; Sarra Boukhris; Mohamed Adnene Laatiri (Leukemia Research Reports)
Burkitt's lymphoma (BL) is an aggressive B-cell lymphoma that occurs in children and adults. It is a chemosensitive lymphoma with very exceptional cases of late relapse.We report the case of a 32-year-old male, originally from a nonendemic area for BL, who was successfully treated for abdominal BL 20 years ago. He described a two-month history of cervical swelling and a one-week history of dyspnea. Physical examination was unremarkable except for a left submandibular mass that extended to the collarbone. An ultrasound of the neck revealed cervical lymphadenopathy. The patient was submitted to a lymph node biopsy with an immunohistochemical analysis, which concluded to the diagnosis of BL. Screening for recent Epstein-Barr-Virus (EBV) infection was negative. We considered this a very late relapse (VLR) of the original disease, and the patient was treated according to the same initial protocol. Unfortunately, he suffered a second relapse and died.We report an unusual case of a VLR of nonendemic BL in an EBV-negative patient, occurring 20 years after achieving complete remission following the initial chemotherapy.